ANALISIS LIKUIDITAS PADA PT.PELAYARAN DUTA LINTAS SAMUDERA DI SAMARINDA - Wijaya, Winda Dwiastuti (EKONOMIA, 2014)
The purpose of this research is to determine the liquidity level of PT.Pelayaran Duta Lintas Samudera in 2011 and 2012. The Analysis tool being used is financial reports analysis with a liquidity ratio. Based on the liquidity study results of PT.Pelayaran Duta Lintas Samudera, it was founded that the liquidity ratio in 2011 to 2012 is decreased, as the current ratio decreased by 11% since 2011 from 22% to 11% in 2012 and the cash ratio increased by 2% since 2011 from 2% to 4% in 2012, then the quick ratio decreased by 1% since 2011 from 11% to 10% in 2012. The derivation of liquidity in PT.Pelayaran Duta Lintas Samudera is due to the increasing of cash and also accompanied by the increasing of current debt, because of that PT.Pelayaran Duta Lintas Samudera to pay or pay off short-term obligations is not quite good